Bioma do Pampa: teoria, pratica & conexão - (:unkn) unknown (Universidade Federal do Pampa, 2026)
The Pampa is a unique biome that occupies about two-thirds of the territory of Rio Grande do Sul and integrates the ecological and cultural identity of the Southern Cone of Latin America. Despite this, it remains invisible in public conservation policies and in the national imagination, compared to other biomes such as the Amazon or the Atlantic Forest. This invisibility results from scientific and historical narratives that have devalued the grasslands as biodiverse environments and constructed the image of an ecological and social void. This chapter seeks to problematize these narratives, presenting the Pampa as a biocultural corridor — a space in which ecological and cultural flows intertwine. The structure is organized into six sections, in addition to this introduction and conclusion: the first discusses the scientific tradition that devalued the grasslands; the second characterizes the physical and physiognomic bases of the biome; the third analyzes its biodiversity; The fourth examines the historical construction of the myth of the “void”; the fifth describes the diversity of peoples and traditional communities; and the sixth proposes reading the Pampa as a biocultural corridor on a local and transboundary scale.
Pampa biome: theory, practice & connection
Keywords: Biomas brasileiros; Pampa; Biologia; Brazilian biomes; Biology; MULTIDISCIPLINAR